Jom Masuk U 2024 East Zone II A Top Destination for School Holidays - Jamilah Bebe, Mohamad; Siti Ainun Jariyah, Hassan (UMPSA, 2024)
GAMBANG, 1 June 2024 – ‘Jom Masuk U 2024’ East Zone II Carnival held at Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) has become a gathering place for various higher education institutions in Malaysia, both public and private.